1995
DOI: 10.1111/j.1467-7717.1995.tb00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Poverty in the Early Stages of Famine: North Darfur, 1988–90

Abstract: In this article we report findings on the relationship between malnutrition and poverty during a period of acute food insecurity in Darfur, Sudan. Children of rich and poor families were equally likely to be malnourished, which is explained in terms of people's responses to the threat of famine. This finding has important implications for targeting interventions in the early stages of famine. Appropriate interventions at the early stages of famine are livelihood and income support to the most vulnerable. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…2003; Morrow 1999). Similarly, studies of past famines suggest that a drought can affect different areas and people within the same stricken area very differently (Mbithi and Wisner 1973; Jaspars and Young 1995). In a recent attempt to conceptualize the way in which components of vulnerability are linked to factors beyond the system of study, Turner et al (2003) emphasize the role of place‐based analysis.…”
Section: Coping and Vulnerabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…2003; Morrow 1999). Similarly, studies of past famines suggest that a drought can affect different areas and people within the same stricken area very differently (Mbithi and Wisner 1973; Jaspars and Young 1995). In a recent attempt to conceptualize the way in which components of vulnerability are linked to factors beyond the system of study, Turner et al (2003) emphasize the role of place‐based analysis.…”
Section: Coping and Vulnerabilitymentioning
confidence: 98%
“…Past studies of drought have observed that households may reduce meals in order to make food stocks last longer and to minimize the exchange of production capital for food. Reduced consumption may also, at a later stage, be a response to complete exhaustion of food stocks and poor alternative sources of food and income (Kennedy 1992; Jaspars and Young 1995). Reconnaissance and key informant interviews gleaned school dropout and reduction of means as relatively reliable indicators of a household being adversely impacted during drought in both sites.…”
Section: The Case Studiesmentioning
confidence: 99%
“…According to an estimate, 159 million under-5 children are stunted globally (Schrijner and Smits, 2018). Malnutrition has become a severe problem in underdeveloped countries and natural disaster affected regions (Jaspars and Young, 1995). Chronic under-nutrition is pervasive in most low-income countries, hit by a natural disaster (Evans and Bassani, 2018), resulting in low levels of human performance.…”
Section: Introductionmentioning
confidence: 99%
“…In African societies, for example, the socio-demographic outcomes of children have been found to be negatively affected by the HIV/AIDS epidemic (e.g. Young and Ansell 2003; Foster and Williamson 2000); wars (Albertyn et al 2003; Veale and Dona 2003); as well as famines (Jaspars and Young 1995). More recently, research on African children affected by these events has drawn attention to their effects on orphan status, and in turn, the effects of orphan status on schooling (e.g.…”
Section: Introductionmentioning
confidence: 99%